2018
DOI: 10.4142/jvs.2018.19.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant-attenuated Salmonella Pullorum strain expressing the hemagglutinin-neuraminidase protein of Newcastle disease virus (NDV) protects chickens against NDV and Salmonella Pullorum challenge

Abstract: Newcastle disease virus (NDV) and Salmonella Pullorum have significant damaging effects on the poultry industry, but no previous vaccine can protect poultry effectively. In this study, a recombinant-attenuated S. Pullorum strain secreting the NDV hemagglutinin-neuraminidase (HN) protein, C79-13ΔcrpΔasd (pYA-HN), was constructed by using the suicide plasmid pREasd-mediated bacteria homologous recombination method to form a new bivalent vaccine candidate against Newcastle disease (ND) and S. Pullorum disease (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…Similar to this, Mass et al (22) revealed the crucial significance of IL-4 to decrease the HPAI in comparison with cellular immunity (IFN-γ), which is shown by the considerable reduction in viral shedding, despite the high pathogenicity and multiplication the virus. The results were in line with those reported by Ke Ding et al (20), who showed that lymphocytes play a role in controlling the host immune response and signaling between protective cells through the production of cytokines, which are soluble particles produced by many cells, including T, B, macrophages, and dendritic cells. S. Pullorum causes a higher Th2-like response than the Th1-type response, that means crucial particularly cellular immune response for the clearance of S. Pullorum post infection (23).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to this, Mass et al (22) revealed the crucial significance of IL-4 to decrease the HPAI in comparison with cellular immunity (IFN-γ), which is shown by the considerable reduction in viral shedding, despite the high pathogenicity and multiplication the virus. The results were in line with those reported by Ke Ding et al (20), who showed that lymphocytes play a role in controlling the host immune response and signaling between protective cells through the production of cytokines, which are soluble particles produced by many cells, including T, B, macrophages, and dendritic cells. S. Pullorum causes a higher Th2-like response than the Th1-type response, that means crucial particularly cellular immune response for the clearance of S. Pullorum post infection (23).…”
Section: Discussionsupporting
confidence: 92%
“…According to reports, creating recombinant live vaccines with attenuated Salmonella not only boosts the immune system's capacity to fight against Salmonella infection but also considerably improves the immunological impact of the exogenous gene carried by the vaccine (18,19). According to these findings, NDV and AIV vaccinations have a high protective impact against S. pullorum infections (20). These findings are consistent with those of Baumgarth et al (21), who showed that the efficient response of Th2 cells to cytokines generated by activated phagocytic cells in mice aids in reducing viral growth in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been claimed that the age of exposure had no effect on Salmonella typhimurium liver recovery (25). The results were consistent with those reported by Ke Ding et al (26), who demonstrated that lymphocytes play a role in regulating the host immune response and the cellular immune response is particularly important for the clearance of S. pullorum because it elicits a higher Th2-like response than the Th1-type response, which is more typically associated with S. typhimurium or S. enteritidis (27). After week 1 pi, the IgG antibody titers to S. pullorum grew and peaked at week 3 pi.…”
Section: Discussionsupporting
confidence: 91%
“…Examples of harmless bacteria include Bacillus subtilis [ 152 , 153 ] and Saccharomycetes [ 154 , 155 ]. Examples of live-attenuated microorganisms that have been widely used as live vaccine vehicles include Salmonella [ 156 , 157 ], Listeria [ 158 , 159 ], poxvirus [ 160 ] and influenza virus [ 161 ]. Li et al constructed a recombinant Lactobacillus -derived vaccine that displayed influenza epitopes (sM2 and HA2) [ 162 ].…”
Section: Development Of Vaccines Against M Pneumoniae mentioning
confidence: 99%